Working Paper 25: High Level Reporting Mechanisms: A comparative analysis (Basel Institute on Governance Working Papers, 2018)
This report discusses the different contexts and processes through which a High Level Reporting Mechanism (HLRM) has been designed and implemented in Colombia, Ukraine, Panama and Argentina, as well as initial interest in the HLRM model in Peru.Its aim is to understand the specificities of each case and draw lessons applicable to future projects in other countries, whilst respecting the commitment to develop an HLRM that takes account of the specific country’s context.
Keywords: High Level Reporting Mechanism; HLRM; Collective Action; procurement corruption; clean procurement; public tenders